Telewizja interaktywna w Polsce (na przykładzie kanału aMazing Multimedia Polska) - Robert Kuciński, Robert Kuciński (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
The article is an attempt to describe the essence of interactive television based on the example of aMazingTV – the first interactive channel in Poland, established by Multimedia Polska in September 2009. The author presents the development of interactivity in life, art and media and reflects on the future of one of the most important features of the so-called new media.